Reference statistics and planning of reference personnel in academic libraries : a case study of the University Putra Malaysia Library, Malaysia / Zubaidah Iberahim, Fuziah Mohd Nadzar and Mohd Hafiz Abdul Salam - Iberahim, Zubaidah; Mohd Nadzar, Fuziah; Abdul Salam, Mohd Hafiz (Faculty of Information Management, 2014)
This study systematically identifies a reference activity to discover the trends and types of user questions/problems posed through traditional means at the RAD service based specifically on the nature of the UPM Main Library from the years 2008 through 2012. This study employs the quantitative research method using the data from the reference enquiry statistics to investigate the emerging trends in reference questions and enquiries in the UPM Main Library. The reference statistics were gathered by the reader advisor who manned the RAD service from the years 2008 through 2012. The compiled reference statistics included all the transactions with any faculty; student; staff, external member or public who had used the RAD service either in person or by telephone. A standard reference statistics form used includes a section to indicate types of reference transaction questions with the following options; directional, ready reference, in-depth reference, and demonstrations. Directional questions refer to questions regarding location of services, branch libraries, people and departments, collections, and materials available in particular sections of the library or the university. Ready reference questions are those questions that could be answered quickly in 3 minutes or less,for instance, questions pertaining to a particular library service, or regarding the facilities available in the library or the library collections. In-depth reference questions are those that require more than 3 minutes to answer, and/or involve the use of several resources, and it may also include a demonstration of the use of printed and online resources as well. The utilized set of statistical data showed a fluctuation in the data of reference enquiries (questions or problems) at Reader's Advisory Desk (RAD) asked through traditional means over the entire 5-year time period.